A Social History of Administrative Science in Italy Planning a State of Happiness from Liberalism to Fascism - Rapini, Andrea (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book traces the origins, life and death of Administrative Science in Italy as an academic discipline between the nineteenth and twentieth centuries. It does so by combining the study of ideas, institutional history, intellectual history and social history. The Faculty of Law first introduced Administrative Science in 1875, with the aim of providing the elite with the necessary tools to distribute wealth more equally, to take care of the population and, thus, to make the young Italian State more legitimate in the eyes of the emerging masses. Law and social sciences were merged with the aim of increasing reforms, including that of creating a State of Happiness for all citizens. Throughout its 70-year existence, Administrative Science was deprived of its contents and scientific independence, and academically overshadowed by Administrative and Public law. Finally, although the liberal elites discarded the reformer project of Administrative Science even before Fascism turned everything upside down, most of the original traits of this knowledge were absorbed into Fascist corporate and totalitarian structures. Andrea Rapini is Professor in Contemporary History at the Department of Education and Humanities, University of Modena and Reggio Emilia, Italy.
1. Introduction -- 2. State Building and the Institutionalization of Administrative Science -- 3. Who Decides what Administrative Science is? -- 4. Administrative Science and Total War -- 5. The Decline of Administrative Science -- 6. Conclusion.
Keywords: Italy-History.; Europe-History-1492-.; Intellectual life-History.; Social history; History of Italy; History of Modern Europe; Intellectual History; History of Ideas; Social History